2019
DOI: 10.1093/jnci/djz001
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Explain Differences in Abstinence Between Black and White Smokers: A Prospective Intervention Study

Abstract: Background Black-white differences in smoking abstinence are not well understood. This trial sought to confirm previously reported differences in quitting between blacks and whites and to identify factors underlying this difference. Methods During enrollment, 224 black and 225 white low-income smokers were stratified on race and within race on age and sex to ensure balance on these factors known to impact abstinence. The inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 93 publications
(80 reference statements)
8
54
0
Order By: Relevance
“…) and PNAT (Fig. ) was explored by including additional covariates which have been found to impact abstinence outcomes . Of the baseline variables that were significant predictors of week 26 abstinence, plasma cotinine was available in both trials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…) and PNAT (Fig. ) was explored by including additional covariates which have been found to impact abstinence outcomes . Of the baseline variables that were significant predictors of week 26 abstinence, plasma cotinine was available in both trials.…”
Section: Resultsmentioning
confidence: 99%
“…The study 1 sample was drawn from Quit2Live, a prospective cohort intervention study with a stratified recruitment based on race (African American, Caucasian), age (< 40, ≥ 40) and gender (male, female) (NCT01836276); these variables were included as covariates in this analysis . Quit2Live was designed to investigate differences in cessation rates between African Americans and Caucasians, and to understand the factors underlying such differences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrimination-unequal or unfair treatment by individuals and/or social institutions on the basis of gender, race, ethnic or national origin, sexual orientation, social class or other factors-is disproportionately experienced by African Americans [5,6] and predicts risk of relapse during cessation attempts [7,8]. African American smokers who experience perceived discrimination more frequently are at greater risk of being a smoker [9], higher tobacco dependence severity [10] and greater motivation to smoke to enhance cognitive functioning and mood [10].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that associations between perceived frequency of discrimination and cigarette smoking status and smoking frequency were amplified among African Americans relative to Latinos [11]. More recently, a 2019 study demonstrated that African American low‐income smokers who reported a greater frequency of exposure to discrimination were less likely to achieve smoking abstinence at week 26 upon receiving interventions that included varenicline for 12 weeks and six guideline‐based smoking cessation counseling sessions relative to African Americans who reported experiencing discrimination less frequently [8]. Furthermore, a 2020 study tested the causal relationship between acute interpersonal discrimination and smoking motivation (i.e.…”
Section: Introductionmentioning
confidence: 99%